PENINGKATAN KECERDASAN SPIRITUAL SISWA MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING MATA PELAJARAN AL-ISLAM - Maulidi, Achmad (Universitas Al-Amien Prenduan, 2020)
The implementation of Islamic Religious Education in educational institutions is currently still traditional, the learning process tends to emphasize the cognitive aspect, namely the school conveys knowledge to students at the estuary just to prepare them to succeed in taking the final exam. Without paying attention to the aspects of personality, psychological, social, physical and mental formation in students.The focus of this research is, first, how is the implementation of al-Islam learning as a means of increasing the Spiritual Intelligence of students at SMA Muhammadiyah I Pamekasan. Second, how is the Contextual Teaching and Learning learning model of al-Islam learning in increasing the Spiritual Intelligence of students at SMA Muhammadiyah I Pamekasan. Third, how are the obstacles faced in implementing the Contextual Teaching and Learning model of al-Islam learning in increasing the Spiritual Intelligence of students at SMA Muhammadiyah I Pamekasan.This research uses a qualitative approach which is intended to understand and describe phenomena, as well as to find the nature that exists and occurs in the research location.It is known that: First, the implementation of al-Islam learning at SMA Muhammadiyah I Pamekasan is quite good although it has not yet reached the stage of perfection. It is based on planned learning with syllabus development design and proper model selection. Besides being based on this, al-Islamic learning is also carried out by inculcating social ethics in reflecting the cognitive domain of religion into an affective domain, for example: social service activities (Baksos) 'idul qurban which aims to establish ukhuwwah al-Islamiyyah, as well as helping the poor. Zakat, Infaq, and Sadaqah. Second, the CTL model on al-Islam subjects in improving student intelligence by connecting teaching materials to the real conditions of students and encouraging students to relate their knowledge to their daily lives. Third, the obstacles faced, among others; different levels of intelligence, level of awareness of students, problems from teachers, problems in terms of time, learning media problems, environmental problems.